Study on coral diversity and distribution at four selected areas in Tioman Island, Malaysia - Khodzori, Mohd Fikri Akmal; Saad, Shahbudin; Mohammad Noor, Normawaty (2013)
Diversity and distribution of corals were investigated in Teluk Benuang, Kampung Genting, Pulau Renggis and Teluk Teduh, Tioman Island. The diversity and distribution of corals in all sampling stations were observed and recorded using Coral Video Transect (CVT) method. The captured images were analyzed using Coral Point Count extension (CPCe) software. The physicochemical parameters were also measured. A total of 32 genera of corals belong to 16 families were recorded. Genus of Acropora and Montipora from family Acroporidae, and Favites from family Faviidae were found dominant. Tlk. Benuang and Tlk. Teduh have shown the highest number of coral genera among the study locations. The Shannon diversity index (H') and evenness index (EH ) of coral genera at Tlk. Benuang were 2.40 and 0.78, respectively while the Shannon diversity index (H') and evenness index (EH•) of coral genera at Tlk. Teduh were 2.33 and 0.77 respectively. As for the depth, 1 Om depth has shown the highest number of coral genera compared to 5m depth. The Shannon diversity index (H') and evenness index (Eh') of coral genera at lOm depth were 2.75 and 0.80, respectively while the Shannon diversity index (H') and evenness index (Eh') of coral genera at 5m depth were 2.47 and 0.79 respectively. The geographical, morphological and depth were the factors that influence the establishment of corals. Chi-square analysis had shown that genus of Acropora, Hydnophora, Plerogyra, Cycloseris, and Ctenactis were not significant differences with locations and depths (p>0.05) meanwhile, the other coral genera were found highly significance with location and depths (p<0.01). Other physicochemical parameters were not shown clearly relationship between coral diversity and distribution.